The transcontinental railroad : connecting the nation - Harasymiw, Therese (New York Lucent Press, 2018)
Readers may know the basic facts about the creation of the first transcontinental railroad, but the full story behind the push to connect the United States by rail is much more than the names and dates taught in history classes. Readers discover the exciting, important details including the contributions of immigrants as they encounter engaging main text, comprehensive sidebars, and historical images that include carefully chosen primary sources. These text features come together to give readers an in-depth look at the first successful attempt to connect the United States through transportation. Black-and-White Photographs, Detailed Table of Contents, Full-Color Photographs, Further Information Section, Index, Maps, Primary Sources, Sidebars, Timelines, Websites.
Setting the scene: a timeline -- Introduction: a railway from coast to coast -- A sprawling nation -- Plotting a course across the continent -- A way to preserve the union -- The Union Pacific heads West -- The Central Pacific heads East -- Epilogue: completely transcontinental.
Includes bibliographical references and index.
12 - 15 years
105950
Keywords: Pacific railroads -- Juvenile literature. -- Railroad - Omaha, NE - Sacramento, CA; Railroads -- United States -- History -- Juvenile literature; .; History; Juvenile works